Practices Regarding Human Papillomavirus and Cervical Cancer in A Sample of Paramedical Staff in Al- Najaf Governorate, Iraq - Alaa Mehdi Salih; Atta Ah Mousa Al –Sarray (Journal of Techniques)
The papillomaviridae viral family includes HPV. When it comes to female sexually transmitted diseases, the genital tract is the primary site of infection for genital type HPVs, which are further divided into high- and low-risk subgroups depending on the likelihood that they will cause cancer of the genital tract. High-risk HPV strains 16 and 18 cause cervical cancer. Sexual contact or skin-to-skin contact is the primary mode of transmission of HPV.